Art, culture, society and aesthetic imaginary: Redimensions from Historical Time and Space notions (Mayéutica Revista Científica de Humanidades y Artes, 2017)
The objective of this essay is to present an exercise of reflection on the notions of art and culture and their relationship with the historical categories of time and space. This argumentative exercise is important and necessary for the study of art products in the field of cultural studies that are in vogue in Latin America and in recent projection in Venezuela, especially in the Central West area of the country. This is a reflection that is organized from a system of authority argumentation based on the debate of some ideas such as those presented by Castoriadis (1997 and 2004), Cassirer (1999), Jameson and Žižek (1998) and Hauser (1975). Methodologically, this essay is organized as a discursive construct based on the hermeneutic approach from which the exegetical technique is used to reach ideas and theoretical argumentative inputs. Among the most distinguished arguments highlight: a) art and culture must be studied in a particular and contextualized way; b) the time and space categories are both indispensable for the study of culture and for research in art products; c) the religious, the historical, the social, the political and the economic can be contained in the products of art and, therefore, they are an expression not only of the individuality of its creators but also of a culturally shared thought; that is, of a collective thought and d) art is the specular reflection of man, his culture, his society, his space and his time.
Keywords: art; culture; space; time; arts products